2016
DOI: 10.5487/tr.2016.32.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Oil Extract Mitigates Testicular Injury Following Adjuvant Treatment with Antiretroviral Drugs

Abstract: Increased access to highly active antiretroviral therapy (HAART) has made the management of drug toxicities an increasingly crucial component of HIV. This study investigated the effects of adjuvant use of coconut oil and HAART on testicular morphology and seminal parameters in Sprague- Dawley rats. Twelve adult male Sprague-Dawley rats, weighing 153~169 g were distributed into four groups (A–D) and treated as follows: A served as control (distilled water); B (HAART cocktail- Zidovudine, Lamivudine and Nevirapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 44 publications
5
35
0
Order By: Relevance
“…In the present study, the testicular ultrastructure of the HAART‐treated rats displayed an abnormally significant increased thickness of basement membrane (refer to Figure a). This actually conforms to our previous work and another study indicating that HAART increases carbohydrate components and contributes to extensive fibrosis around the basement membrane (Azu et al., ; Ogedengbe et al., ). As the entire basement membrane is made of extracellular matrix, interactions between the matrix, tubular wall and germinal cells will contribute significantly to normal testicular development (Favorito, Hidalgo, Pazos, Costa, & Sampaio, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the testicular ultrastructure of the HAART‐treated rats displayed an abnormally significant increased thickness of basement membrane (refer to Figure a). This actually conforms to our previous work and another study indicating that HAART increases carbohydrate components and contributes to extensive fibrosis around the basement membrane (Azu et al., ; Ogedengbe et al., ). As the entire basement membrane is made of extracellular matrix, interactions between the matrix, tubular wall and germinal cells will contribute significantly to normal testicular development (Favorito, Hidalgo, Pazos, Costa, & Sampaio, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, we report, for the first time, the role of VCO in alleviating HAART‐induced testicular ultrastructural alterations. Our previous work on the testicular histomorphology and seminal fluid parameters revealed that VCO mitigated HAART‐induced alterations in male Sprague‐Dawley rats (Ogedengbe et al., ). Accumulating evidence has also shown that VCO is effective in improving semen parameters (Dosumu et al., ), enhances insulin secretion, lower lipid levels in serum and tissues, and could alleviate other pathological conditions (Rahim et al., ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thickening of basement membrane and excessive deposition of extracellular matrix proteins are characteristics of fibrotic disorders of multiple organs including liver and kidney (Rosenbloom et al, 2010). In rats, PAS staining was used as a histomorphological method to detect disorders in seminiferous tubular histoarchitecture (Ogedengbe et al, 2016). In the present study, both candesartan and lorsartan modulated the TAA-induced testicular toxicity and all histological and immunohistochemical alteration in both testicular tissue and cauda epididymis tubules with non-significant differences in-between.…”
Section: Discussionmentioning
confidence: 54%